2008
DOI: 10.1182/blood-2008-01-132134
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma-derived Dickkopf-1 disrupts Wnt-regulated osteoprotegerin and RANKL production by osteoblasts: a potential mechanism underlying osteolytic bone lesions in multiple myeloma

Abstract: Multiple myeloma (MM) is characterized by osteolytic bone lesions (OBL) that arise as a consequence of osteoblast inactivation and osteoclast activation adjacent to tumor foci within bone. Wnt signaling in osteoblasts regulates osteoclastogenesis through the differential activation and inactivation of Receptor Activator of Nuclear factor Kappa B Ligand (RANKL) and osteoprotegerin (OPG), positive and negative regulators of osteoclast differentiation, respectively. We demonstrate here that MM cell-derived DKK1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
189
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(196 citation statements)
references
References 54 publications
2
189
0
5
Order By: Relevance
“…OBs secrete receptor activator of NF-kB ligand (RANKL), a critical growth factor for OCs, and osteoprotegerin (OPG), a soluble RANKL inhibitor. The balance between RANKL and OPG modulates osteoclastogenesis and MM cells typically increase the RANKL/OPG ratio [17,18] promoting OC development.…”
Section: Pathogenesis Of Osteoblast Inhibition In MMmentioning
confidence: 99%
See 1 more Smart Citation
“…OBs secrete receptor activator of NF-kB ligand (RANKL), a critical growth factor for OCs, and osteoprotegerin (OPG), a soluble RANKL inhibitor. The balance between RANKL and OPG modulates osteoclastogenesis and MM cells typically increase the RANKL/OPG ratio [17,18] promoting OC development.…”
Section: Pathogenesis Of Osteoblast Inhibition In MMmentioning
confidence: 99%
“…Most likely, the effects are mediated by the non-canonical Wnt signaling pathway since DKK1 levels are independent from β-catenin activation status [31,32]. In addition, MMderived DKK1 inhibits OPG expression in OBs and upregulates RANKL secretion [18], therefore stimulating osteoclastogenesis. Neutralizing antibodies against DKK1 promote OB differentiation [30] and limit MM cell proliferation when co-cultured with BMSC [33].…”
Section: Pathogenesis Of Osteoblast Inhibition In MMmentioning
confidence: 99%
“…35 -38 Myeloma cells do induce production of high levels of RANKL by marrow stromal cells through adhesive interactions between 4 1 integrin on myeloma cells and vascular cell adhesion molecule-1 (VCAM-1) on marrow stromal cells, 39 as well as by soluble factors produced by myeloma cells, such as TNF- 28,40 and Dickkopf1 (DKK1). 41 Further enhancing the effects of increased RANKL in myeloma is the decreased production of OPG by marrow stromal cells via inhibition of osteoblast differentiation, decreased transcription of OPG and degradation of OPG by myeloma cell endocytosis of the OPG bound to CD138 (syndecan-1). 42,43 Thus, the ratio of RANKL to OPG in myeloma patients is markedly increased and drives osteoclastogenesis.…”
Section: Factors Driving Osteoclast Formation and Activity In Mmbdmentioning
confidence: 99%
“…86 DKK1 can enhance RANKL production as well as suppress OPG expression, further driving the bone-destructive process. 41 Preclinical studies with blocking antibodies to DKK1 (BHQ880) have clearly shown that they can enhance bone formation and block tumor growth in murine models of myeloma bone disease. 87 Anti-DKK1 does not have direct anti-tumor effects, although anti-DKK1 may suppress tumor growth via its effects on osteoblast differentiation.…”
Section: Dickkopf1mentioning
confidence: 99%
“…This phenomenon has been already described in myeloma where Dkk1 produced by myeloma cells reduces osteoblast function but also increases the production of RANKL and decreases the production of OPG by stromal cells, and thus leads to increased bone resorption. 15 Furthermore, in patients with rheumatoid arthritis, Dkk1 directly impaired new bone formation through the reduction of osteoblast function and the decreased production of OPG, which shifted the RANKL/OPG ratio in favor of bone resorption. 16 Thus it seems that Dkk1 inhibits bone formation while promoting bone resorption in different bone disorders and supports the notion that Dkk1 is a key molecule in bone biology.…”
Section: Resultsmentioning
confidence: 99%